Mismatch in the labor market and inflation: an integrative model estimated for the spanish case during the great recession - Ruesga, Santos M. (2018)
The Great Recession has emphasized the need for different economic policies and structural reforms to boost economic growth and advanced emergent economies. This paper is founded on a relatively innovative theoretical concept: the Modified Output Gap (MOG). Based on the Phillips and Beveridge curves, the MOG reveals an explicitly positive relationship between the job vacancy rate and the inflation rate. Empirically, the relationship is estimated by developing three different panel data models: Fixed Effects (FE), Random Effects (RE) and Generalized Method of Moments (GMM). Results shows that a mismatch in the efficiency of the labor market combined with an increased demand in goods and services markets will increase inflation. This paper shows the empirical relevance of the modified output gap for Spain during the Great Recession and how it affects the implementation of the economic stimulus plan led by the Spanish government to boost the economy in this period.